The Impact Of Psychological Characteristics On The Effectiveness Of Motivational Interviewing Based Psychological Counseling - Raimonda Petroliene; Liuda Sinkariova; Dalia Karpovaite; Loreta Zajanckauskaite-Staskeviciene; Jurga Misiuniene; Laura Alciauskaite (European Scientific Journal, ESJ, 2016)
It is well known that in order to control the morbidity and mortality of cardiovascular disease patients, their lifestyle should be taken into account (American Heart Association, 2012; Klumbiene et al., 2002). Studies of various disease patients’ manners (Knight et al., 2006; Thompson et al., 2011) confirm that motivational interviewing (Miller & Rollnick, 2013) is an effective method for changing unhealthy behavior. Nevertheless, our practical experience of motivational interviewing based psychological counseling with rehabilitation hospitals’ cardiac patients’ (Sinkariova et al., 2015) revealed noteworthy observations about some participants lack of motivation to change unhealthy behavior. This observation encouraged us to start a study with the aim to find out if cardiac rehabilitation participants’ personality traits and emotional state are related to the effectiveness of motivational interviewing based psychological counseling. The study used a quasi-experiment where cardiac rehabilitation patients were assigned to control (regular rehabilitation, n=55) or experimental (rehabilitation plus motivational interviewing based psychological counseling intervention, n=64) groups. A total of 119 participants (male=83, female=36, M age=60.47, SD=8.762) attended a survey, which included NEO-FFI, HADs, and “Readiness to change questionnaire” at the beginning and end of cardiac rehabilitation. Nonparametric data analysis showed that patients’ personality traits are not related to the effectiveness of motivational interviewing based counseling, whereas depression is positively related to the effectiveness of intervention to change alcohol consumption. Conclusions/Implications: Depression as an expression of emotional state is an important feature for the effectiveness of motivational interviewing based counseling to change cardiac patients’ alcohol consumption. Further understanding of relationships between psychological characteristics and the effectiveness of intervention could help to improve cardiac diseases prevention, treatment, and rehabilitation.